2017
DOI: 10.3762/bjnano.8.196
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of Si between MoS2 layers

Abstract: We report a combined experimental and theoretical study of the growth of sub-monolayer amounts of silicon (Si) on molybdenum disulfide (MoS2). At room temperature and low deposition rates we have found compelling evidence that the deposited Si atoms intercalate between the MoS2 layers. Our evidence relies on several experimental observations: (1) Upon the deposition of Si on pristine MoS2 the morphology of the surface transforms from a smooth surface to a hill-and-valley surface. The lattice constant of the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 64 publications
(58 reference statements)
3
24
0
Order By: Relevance
“…Concerning the chemical nature of the intercalated silicon, several papers report the formation of metal silicides after silicon deposition and annealing on graphene supported on metallic substrates, 5,[16][17][18][19][20]24,25 while others describe the possible formation of silicene [12,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the chemical nature of the intercalated silicon, several papers report the formation of metal silicides after silicon deposition and annealing on graphene supported on metallic substrates, 5,[16][17][18][19][20]24,25 while others describe the possible formation of silicene [12,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 2(d [18] and by van Bremen et al [30] where Si has been deposited on a MoS2 inert substrate and STM images showed no lattice parameter enlargement occurring on silicene formation. While the former interpreted these data in terms of a squeezing of the silicene lattice producing a huge buckling, the latter suggested that a silicene layer intercalation occurred under the first atomic layer of MoS2.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the computational modelling of the electronic bands, so-grown silicene proves to be metallic in character as resulting from direct evidence of the local density of states [9]. Recently, this picture has been objected by figuring out silicon intercalation in between the upmost adjacent MoS 2 layers [27]. Intercalation of silicon atoms inside layered materials to form a self-organized silicene layer is an emerging topic of study in a number of combinations; however, many factors in the silicon growth processing as well as in the affinity of silicon with underlying substrate may affect the details or the emergence of the intercalation.…”
Section: Discussionmentioning
confidence: 56%